THE EFFECT OF DRY LAND TRAINING MODEL ON YOUTH ATHLETES SWIMMING PERFORMANCE DURING COVID-19 PANDEMIC - Subekti, Rosswaqiah Darazat (Universitas Negeri Semarang, 2021)
The aims of this study were to examine the effects of the dryland training model on swimming performance in youth athletes duning covis-19 pandemic. The covid-19 pandemic affects the physical condition and performance of athletes, therefore these athletes need to maintain physical fitness by continuing to practice even with limitations in carrying out sports activities. The dryland training model was a training on land which aimed to improve physical and performance components in the form of strength, flexibility, agility, aerobic endurance, and speed also as an alternative training model on pandemic situation. The method used in this research is an experimental method (Experimental Design) with a One Group Pretest-Posttest Design with a sample of 30 youth athletes (17 male and 13 female) drawn from the population using total sampling technique. The instrument used in this study was the 50 meter freestyle swimming test. The results of this study indicate that there is a significant effect of the dryland training model on the swimming performance of youth swimming athletes during the covid-19 pandemic and the dryland training model provides an increase in swimming time of 50 meters freestyle.